Adverse side‐effects of dexamethasone in surgical patients – an abridged Cochrane systematic review. (1st March 2019) - Polderman, J. A. W.; Farhang‐Razi, V.; van Dieren, S.; Kranke, P.; DeVries, J. H.; Hollmann, M. W.; Preckel, B.; Hermanides, J.
Summary: In the peri‐operative period, dexamethasone is widely and effectively used for prophylaxis of postoperative nausea and vomiting. The objective of this meta‐analysis was to assess the adverse effects of an incidental steroid load of dexamethasone in adult surgical patients. We searched in MEDLINE, Embase, the Cochrane Central Register of Controlled Trials and the Web of Science for randomised controlled trials comparing an incidental steroid load of dexamethasone with a control intervention in adult patients undergoing surgery. Two review authors independently screened studies for eligibility, extracted data and assessed all included studies for bias. Our primary outcomes were postoperative systemic or wound infection, delayed wound healing and glycaemic response within 24 h. We included 37 studies in this meta‐analysis. The pooled results found no evidence that dexamethasone increased the risk of a postoperative wound infection, Peto OR (95%CI) 1.01 (0.80–1.27); 4603 participants, 26 studies; I² = 32%; moderate‐quality evidence. Whether dexamethasone influenced wound healing was unclear due to the large confidence intervals, Peto OR (95%CI) 0.99 (0.28–3.43); 1072 participants, 8 studies; I² = 0%; low‐quality evidence. Dexamethasone produced a mild increase in glucose levels among participants without diabetes during the first 12 h after surgery, mean difference (95%CI) 0.7 mmol.l −1 (0.3–1.2) 10 studies; 595 participants; I² = 50%; low‐quality evidence. This article is an abridged version of a Cochrane Review.